2014
DOI: 10.1021/ic501039n
|View full text |Cite
|
Sign up to set email alerts
|

H-bonded adducts of [2,4,6-{(C10H21O)3C6H2NH}3C3N3] with [LnM{PPh2(C6H4CO2H)}] displaying Columnar Mesophases at Room Temperature

Abstract: Displacement of a labile ligand from appropriate precursor complexes by 2- or 4-PPh2C6H4COOH yields neutral gold(I) and gold(III) [AuXn(PPh2C6H4COOH)] (n = 1, X = Cl; n = 3, X = C6F5), cationic gold(I) [Au(PPh2C6H4COOH)2](CF3SO3), and neutral chromium(0) [Cr(CO)5(PPh2C6H4COOH)] metallo-organic acids. [AuCl(4-PPh2C6H4COOH)], [Au(C6F5)3(4-PPh2C6H4COOH)], and [Cr(CO)5(2-PPh2C6H4COOH)] have dimeric structures with typical carboxylic H-bond bridges, whereas [Au(C6F5)3(2-PPh2C6H4COOH)] gives a monomeric species with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 101 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, complexity and diversity can be easily added by introducing additional functionalities within the supramolecular architecture by using complementary acids bearing redox-active units, dyes, radicals or metallic fragments. 51,58 Experimental section…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, complexity and diversity can be easily added by introducing additional functionalities within the supramolecular architecture by using complementary acids bearing redox-active units, dyes, radicals or metallic fragments. 51,58 Experimental section…”
Section: Discussionmentioning
confidence: 99%
“…57 Furthermore, the sigma-bonded tris(triazolyl)benzene central core is not that favorable to mesomorphism, as it is not planar and excludes the possibility for strong p-p interactions. 51,58 This fragment is however a good hydrogen-bonding acceptor, 32 which can react with carboxylic acids and form flat supramolecular complexes, since the H-bonds will pull the triazole rings back to the benzene plane. Hence, additional p-p interactions might appear and foster columnar mesomorphism.…”
Section: Supramolecular Liquid Crystals By Complementary Hydrogen Bon...mentioning
confidence: 99%
“…[22][23][24][25][26][27] Within the past two decades seminal works by Kato, Fréchet, Lehn and Percec [7][8][9][28][29][30][31][32][33][34][35][36][37] have demonstrated that selfassembled LCs have a broad application potential in scientic and technological elds due to mimicking the efficient selfassembly process of nature. [38][39][40][41][42][43][44][45] In contrast to their covalent pendants, supramolecular star mesogens are more exible and may show more complex mesostructures (see for instance Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of 2-(diphenylphosphino)benzoic acid, Ph 2 (o-BzOH)P, with equimolar amounts of (tht)AuCl (tht = tetrahydrothiophene) leads to the formation of 2-(diphenylphosphino)benzoic acid gold(I) chloride, Ph 2 (o-BzOH)PAuCl, 1-Cl. It should be mentioned that various gold(I) complexes bearing a diphenylphosphino-benzoic acid-both ortho and para-have been reported, among them also 1-Cl [56][57][58][59]. Through metathesis with KBr and KI the bromido and iodido congener 1-Br and 1-I are easily accessible.…”
Section: Synthesismentioning
confidence: 99%